An HRA-based simulation model for the optimization of the rest breaks configurations in human-intensive working activities. Issue 3 (2015) - Pasquale, Valentina Di; Miranda, Salvatore; Iannone, Raffaele; Riemma, Stefano
Abstract: Human errors in the workplace can have serious consequences such as accidents, malfunctions and quality defects in the performed task. The Simulator for Human Error Probability Analysis (SHERPA), recently proposed in literature, is able to estimate human reliability for different workplaces and to assess the impact of context via performance shaping factors (PSFs). SHERPA is not limited to the reliability assessment, as many existing HRA methods, but uses it in the operator recovery modelling and breaks scheduling simulation. The paper proposes a SHERPA-based methodology able to determine the rest breaks configuration which minimizes the costs associated with any type of error. More specifically, the model identifies the number, the relative time in shift and the duration of the work suspensions in order to ensure the operator's psychophysical recovery and consequently his optimal increase of reliability. The model has been applied to a case study showing interesting results in terms of economic effects of different breaks configurations.